Development of motor functions in children with autism spectrum disorders - Repina, A.I.; Timofeeva, I.V.; Salimov, M.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the development of motor functions in children with autism spectrum disorders. Methods and structure of the study. The educational experiment was conducted on the basis of two institutions: the theoretical part – at the Department of Theory and Methodology of Adaptive Physical Education of Yekaterinburg Institute of Physical Culture (branch) of Ural State University of Physical Culture (UralSUPC), the practical part – at the Autism Therapy Center «Aurora», Yekaterinburg. Motor tests were used to rate the level of development of motor functions in children with autism spectrum disorders, including the level of motor skills and physical abilities according to age. Results and Conclusion. The application of the methodology of development of motor functions in the children with autism spectrum disorders, taking into account their individual abilities, significantly improves their physical development and has a positive effect on the complex of morphofunctional properties of the body. It also helps to enhance the children’s physical capacities, build and strengthen their motor skills.